Malaysian Agricultural Development and Productivity - Fatimah Said; Saad Mohd Said; Azimah Haji Othman (Indonesian Management and Accounting Research, 2006)
This paper analyzes the long run changes of aggregate input-output relationships and assesses the impact of agricultural development on the growth rate of Malaysian agricultural productivity over the period 1966-2000. We find that despite the intensified effort to modernize and revitalize the agricultural sector, the average annual growth rate of agricultural production decreased from 8.2 percent in the initial phase of agricultural development (1966-1970) to 5.1 percent in the intermediate phase (1971-1990) and subsequently to 0.3 percent in the modernization phase (1991-2000). During 1966-2000, labor productivity recorded the highest annual rate of growth of 4.6 percent as compared to 2.1 percent of land productivity and 2.9 percent of total productivity. All productivity measures recorded an increasingly slower rate of growth throughout the period of study. This reflects the deterioration in production efficiency in Malaysian agriculture presumably due to technological adjustment and inputs subsidies.